Zoogeography of Nepalese amphibians and reptiles - Das, Indraneil; Kastle, Werner; Schleich, H. Hermann; Anders, Christiane (A.R.G. Ganter Verlag K.G, 2002)
Presents an up-to-date view on Nepal's herpetofauna. General chapters cover aspects of zoogeography, herpeto - ethology and conservation. Each species is treated comprehensively, including the essentials of morphology, ecology, systematics, and zoogeography. The geographic distribution of each species is presented in two ways: in a grid map of Nepal and in a regional map.